1989
DOI: 10.1161/01.str.20.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in antithrombotic effect of aspirin.

Abstract: A number of clinical trials suggest that the antithrombotic effect of aspirin is limited to men. To test the possibility that this is due to a sex difference in the inhibitory effect of aspirin on platelet behavior, we studied whole-blood platelet aggregation in men and women and in male patients with carcinoma of the prostate receiving hormone therapy. The in vitro inhibitory effect of aspirin on so-called spontaneous platelet aggregation induced by stirring whole blood and monitored by the decrease in the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 19 publications
3
27
0
3
Order By: Relevance
“…For this reason, the bioavailability of acetylsalicylic acid in women under hormonal contraception seems to be similar to men. It has been also highlighted the importance of sex hormone-mediated modulation of the aspirin activity, by the evidence that the rate of aspirin absorption is declined during the menstrual mid-cycle, and the effects of exogenous hormones on the pharmacokinetics of aspirin have confirmed this finding [36] 3. Gender-difference in anti-platelet drug response…”
Section: Gender-difference In Anti-platelet Pharmacodynamics and Pharmentioning
confidence: 99%
“…For this reason, the bioavailability of acetylsalicylic acid in women under hormonal contraception seems to be similar to men. It has been also highlighted the importance of sex hormone-mediated modulation of the aspirin activity, by the evidence that the rate of aspirin absorption is declined during the menstrual mid-cycle, and the effects of exogenous hormones on the pharmacokinetics of aspirin have confirmed this finding [36] 3. Gender-difference in anti-platelet drug response…”
Section: Gender-difference In Anti-platelet Pharmacodynamics and Pharmentioning
confidence: 99%
“…An in vitro study evaluating whole blood platelet aggregation revealed that the antithrombotic effect of aspirin was significantly greater in men, most likely because of the difference in testosterone levels. 13 In contrast, an estrogen-associated reduction in the number of pituitary receptors for corticosteroids has been observed in female rats. 14 No study has yet examined the effect of gender on corticosteroid pharmacodynamics in humans.…”
mentioning
confidence: 97%
“…1 These age and gender bias could influence the results. 38,39 In conclusion, P-selectin expression, but not activated GPIIb/IIIa, was augmented in ADP-activated platelets in patients in the active stage of TA with conventional therapy. Platelet P-selectin may play an important role in the inflammatory and thrombotic disease process associated with intractable TA by inducing platelet -leukocyte interactions.…”
Section: Discussionmentioning
confidence: 85%